1983
DOI: 10.7164/antibiotics.36.1045
|View full text |Cite
|
Sign up to set email alerts
|

Immunoactive peptides, FK-156 and FK-565. I. Enhancement of host resistance to microbial infection in mice.

Abstract: The protective effect of an immunoactive peptide, D-lactoyl-L-alanyl-r-D-glutamyl-(L)meso-diaminopimelyl-(L)-glycine (FK-156) and a related compound, heptanoyl-r-D-glutamyl-(L)meso-diaminopimelyl-(D)-alanine (FK-565) was determined in mice with various kinds of microbial infections. FK-156 and FK-565 were given to mice either subcutaneously or orally before challenge. The drugs enhanced significantly the defense of mice against acute systemic infections induced by various extracellular and facultative intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Because Nod1 stimulation is also protective against several types of bacteria (17,(27)(28)(29)(30) and prestimulation by synthetic Nod1-stimulating compounds before infection confers resistance against multiple pathogens (33), it will be interesting to test whether local administration of Nod1 agonists such as KF1B will be beneficial in the prevention or treatment of C. difficile-induced pseudomembranous colitis. Nod1 stimulation is known to predominantly stimulate nonimmune cells that lack the ability to secrete potentially harmful cytokines such as TNF and IL-1, which is consistent with the observation that Nod1 stimulants induce chemokines and antimicrobial proteins without causing severe inflammation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Because Nod1 stimulation is also protective against several types of bacteria (17,(27)(28)(29)(30) and prestimulation by synthetic Nod1-stimulating compounds before infection confers resistance against multiple pathogens (33), it will be interesting to test whether local administration of Nod1 agonists such as KF1B will be beneficial in the prevention or treatment of C. difficile-induced pseudomembranous colitis. Nod1 stimulation is known to predominantly stimulate nonimmune cells that lack the ability to secrete potentially harmful cytokines such as TNF and IL-1, which is consistent with the observation that Nod1 stimulants induce chemokines and antimicrobial proteins without causing severe inflammation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Severe combined immunodeficiency (SCID) mice developed weaker but significant arteritis, suggesting a partial involvement of acquired immunity in the inflammation induced by a pure Nod1 ligand, whereas no arteritis was observed in Nod1-knockout mice (Supplemental Table IB and Figure 2B). As FK565 is highly stable and effective by parenteral and oral routes, 16 FK565 was orally administered (Supplemental Table IC). All BALB/c mice showed coronary arteritis/valvulitis after oral administration of 6 days (100 g/day) per week of FK565 with LPS priming, and the severity of coronary arteritis/valvulitis increased with the duration of the administration.…”
Section: Nod1 Ligands Induce Site-specific Inflammation In Vivo In Micementioning
confidence: 99%
“…On the basis of the fact that a Nod1 agonist, FK565, is very stable against temperature and acid, 16 coronary arteritis was successfully induced by oral administration of FK565. This is the first coronary arteritis animal model induced by oral administration of a pure synthetic Nod1 ligand.…”
Section: Nishio Et Al Nod1 Related To Vascular Inflammation 1097mentioning
confidence: 99%
“…A more penetrating study will be performed to characterize the active component of the peptide fraction. Another peptide, FK-565 (heptanoyl-y-Dglutamyl-(L)-meso-diaminopimelyl-(D)-alanine) has been shown to be active against microbial infection in mice (Mine et al, 1983a;1983b). Kitao & Yoshida (1986) found that the FK-565 peptide induced protection against intraperitoneal Aeromonas salmonicida infection in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%